Retrospective evaluation of patients with primary mediastinal large B-Cell lymphoma: Real life experience - Guven, Zeynep Tugba; Celik, Serhat; Kaynar, Leylagul; Keklik, Muzaffer; Eser, Bulent; Cetin, Mustafa; Unal, Ali (Annals of Medical Research, 2021)
Aim: Primary mediastinal large B-cell lymphoma (PMBCL) is a type of lymphoma that forms approximately 3 % of non-Hodgkin lymphomas that often encounter with mass. The aim of this study was to present the epidemiological characteristics, response rates of the treatment and the survival of PMBCL patients in our single center. Materials and Methods: Patient demographics, treatment regimens, survival rates of PMBCL patients were retrospectively analyzed. Results: There are 15 patients in our study. Most of the patients were female (n:9, 60%). The median age at the time of diagnosis was 35.4. Nine patients applied with a bulky lesion in the mediastinum. Most of the patients have been treated with DA-EPOCH-R (dose-adjusted etoposide, doxorubicin, cyclophosphamide, vincristine and prednisone with rituximab) (n:13, 87%) and 2 (n:2, 13%) patients have been treated with R-CHOP (doxorubicin, cyclophosphamide, vincristine and prednisone with rituximab) regimens for 6 cycles. Eight patients (53.3%) received involved-field radiotherapy on the mediastinum. After the first-row chemotherapy, total remission rate was 93.3%. Thirteen (87%) of the patients were still in remission and alive. The median follow-up time in our study was 43 months (13 -81). Mean disease-free survival was 67.43 months and overall survival was 72.87 months. The overall and disease-free survival rate was 86.7 % and 80%. Conclusions: In our study, most patients responded to the treatment and are still being followed in remission.